2019
DOI: 10.3390/ijerph16183305
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Prevalence of Induced Abortion in the Floating Population in Major Cities of China 2007–2014

Abstract: Objective: Our aim was to assess the changes in induced abortion in different migrant groups in China between 2007 and 2014 and the contraceptive methods used prior to induced abortion. Methods: The studies of two population-based cross sections were conducted in urban China, involving 9146 sexually active migrant women. Within the selected sociodemographic subgroups, the changes in the percentage of women who had induced abortions, the proportion of pregnancies ending in induced abortions, the causes of induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
(28 reference statements)
2
14
1
Order By: Relevance
“…The women in the 40-49 age group had a much higher percentage of induced abortion(38.12%) and repeated abortion(28.15%). It was consistent with the ndings of other studies due to the experience undergoing the one-child policy during their reproductive age [12,14,15].Although the proportion of induced abortion in women under 20 was lower than that in women over 20-years of age(12.5% vs 30.9%), the proportion of repeated induced abortion was higher in the the former group(25% vs 20.45%). In particular, 66.7% of them were unmarried.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The women in the 40-49 age group had a much higher percentage of induced abortion(38.12%) and repeated abortion(28.15%). It was consistent with the ndings of other studies due to the experience undergoing the one-child policy during their reproductive age [12,14,15].Although the proportion of induced abortion in women under 20 was lower than that in women over 20-years of age(12.5% vs 30.9%), the proportion of repeated induced abortion was higher in the the former group(25% vs 20.45%). In particular, 66.7% of them were unmarried.…”
Section: Discussionsupporting
confidence: 91%
“…The abortion rate in our study was close to that reported in three major cities in china [12]. The percentage of married women and unmarried women experiencing one induced abortion was about 32.78% and 17.18% respectively, and 11.72% of unmarried women and 21.28% of married women experienced the repeated induced abortion.…”
Section: Discussionsupporting
confidence: 84%
“…Although conception is not normatively expected in the transition from cohabitation to marriage in contemporary China (Wang et al 2019), the rise of cohabitation since the 1980s nevertheless parallels an upsurge of premarital pregnancies carried to term in marriage (Ma and Rizzi 2017). The demographic characteristics of Chinese women who conceived their first births outside of marriage indicate that this fertility-accelerating effect of cohabitation is associated with the tradition of early marriage and childbearing, mixed with low rates of contraceptive use (Qian, Tang, and Garner 2004), a high incidence of unintended pregnancies (UNESCO and UNFPA 2018), and a strong belief in fatalism (Herrmann-Pillath 2006).…”
Section: The Linkage Of Cohabitation To the Timing Of First Birth In Chinamentioning
confidence: 99%
“…The wide availability of health facilities for induced abortions (Qian, Tang, and Garner 2004), coupled with the most lenient abortion laws in the world (Cao 2015), undoubtedly helps curtail any further growth (if not a notable decline) of this fertilityaccelerating effect of cohabitation, enabling premaritally pregnant Chinese women to avoid hurrying into an unplanned marriage (Wang et al 2019). Evidence regarding the mediating role of contraceptive use is spare and less consistent, with some studies indicating no change in contraceptive practice in the transition to cohabitation (Gao, Tu, and Yuan 1997), while more recent studies revealed an active search for modern contraceptives among young women who are most likely to cohabit before marriage (Decat et al 2011).…”
Section: The Linkage Of Cohabitation To the Timing Of First Birth In Chinamentioning
confidence: 99%
“…Recent evidence suggested that the floating population in China was characterized by stigma and discrimination ( 2 ), poor psychological and social health ( 3 ), poor sense of belonging ( 4 ), and high prevalence of induced abortion ( 5 ). It has previously been observed that they exhibited poor awareness of reproductive health ( 6 ) and lived in poor living environment ( 7 ).…”
Section: Introductionmentioning
confidence: 99%